Ṣuḥuf-i Ibrāhīm : taẕkirah-ʼi shuʻarā-yi Fārsī (sadah-ʼi davāzdahum) - Khalīl, ʻAlī Ibrāhīm Khān, -1851 or 1852 ([Khudā Bakhsh Oriyanṭal Pablik Lāʼibrayrī], 1978)
Biographical dictionary of the 18th century Persian poets from India.